2022
DOI: 10.1007/s00436-022-07733-y
|View full text |Cite
|
Sign up to set email alerts
|

Enterocytozoon bieneusi in fecal samples from calves and cows in Austria

Abstract: Enterocytozoon bieneusi is an obligate intracellular pathogen that infects livestock, companion animals, and wildlife and has the potential to cause severe diarrhea especially in immunocompromised humans. In the underlying study, fecal samples from 177 calves with diarrhea and 174 adult cows originating from 70 and 18 farms, respectively, in Austria were examined for the presence of E. bieneusi by polymerase chain reaction targeting the Internal Transcribed Spacer 1 (ITS1) region. All positive samples were fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…The present study showed that the infection rate of E. bieneusi in calves from Ningxia was 10.0% (44/438), which is similar to that reported in other studies for cattle in China and several other countries [45][46][47][48][49]. On the other hand, in the present study, although there was no certain association between diarrhea and the prevalence of E. bieneusi infection, E. bieneusi genotypes were more diverse in diarrheic calves than in non-diarrheic calves, with all four genotypes found in diarrheic calves, while only the J genotype was found in non-diarrheic calves.…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed that the infection rate of E. bieneusi in calves from Ningxia was 10.0% (44/438), which is similar to that reported in other studies for cattle in China and several other countries [45][46][47][48][49]. On the other hand, in the present study, although there was no certain association between diarrhea and the prevalence of E. bieneusi infection, E. bieneusi genotypes were more diverse in diarrheic calves than in non-diarrheic calves, with all four genotypes found in diarrheic calves, while only the J genotype was found in non-diarrheic calves.…”
Section: Discussionsupporting
confidence: 90%